2017
DOI: 10.5152/eurjrheum.2016.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of olfactory function in Behçet’s disease

Abstract: Objective: Behçet's disease (BD) is a chronic, relapsing type of vasculitis of unknown etiology and is characterized by oral and urogenital ulcers and ocular inflammation with cutaneous, musculoskeletal, vascular, and nervous system manifestations. Few cases involving the nasal mucosa have been reported in the literature, and the true prevalence of BD remains unknown. Neurological involvement associated with BD might play a more important role in causing olfactory dysfunction than mucosal involvement, but suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…In the present study, olfactory bulb volume and olfactory sulcus depth were evaluated in patients with Behçet's disease. A scan of the literature revealed studies that evaluated olfactory function in Behçet's disease using olfactory or smell tests 1 , 19 , 20 . However, to the best of our knowledge, there has been no previous study of MRI measurements of olfactory bulb volume and olfactory sulcus depth in Behçet's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, olfactory bulb volume and olfactory sulcus depth were evaluated in patients with Behçet's disease. A scan of the literature revealed studies that evaluated olfactory function in Behçet's disease using olfactory or smell tests 1 , 19 , 20 . However, to the best of our knowledge, there has been no previous study of MRI measurements of olfactory bulb volume and olfactory sulcus depth in Behçet's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Behçet's disease is a multisystem vasculitis, characterised by mucosal aphthous lesions, mainly in the oral and genital mucosa 1 . Akyol et al 1 . reported that olfactory dysfunction may denote neurological involvement in Behçet's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Be that as it may, neural improvement and separation inside the olfactory system is yet to be totally clarified 14 . Although frequently dismissed by patients and clinicians, the olfactory sense is of most extreme significance to people, since it contributes fundamentally to wellbeing and personal satisfaction 15 .…”
Section: Olfactory Dysfunctionmentioning
confidence: 99%
“…Akyol et al 15 assessed the olfactory capacity of patients diagnosed with BD. "Odor identification scores" were essentially lower in the BD group compared to the control group.…”
Section: Nasal and Olfactory Manifesta-tions In Bdmentioning
confidence: 99%
“…The average age of onset is during the early 30s, and the male to female ratio differs depending on ethnicity (1). BD is more prevalent in the Far East, the Mediterranean, and the Middle East (2).…”
Section: Introductionmentioning
confidence: 99%